Kurikulum Deep Learning di Indonesia; Sebuah Harapan Baru - Wijaya, Mulyadi (Fakultas Sastra Universitas Ekasakti, 2025)
Discussing deep learning, not just talking about Mindful, meaningful and joyful learning. However, there is a further leap regarding educational transformation. The history of applying deep learning in the classroom reflects a long journey from initial theory to transformational practical applications. Despite facing many challenges, this technology continues to develop and offers great potential to revolutionize learning. With the right investment in research and infrastructure, the future of deep learning-based education will become brighter. The deep learning curriculum in Indonesia must be designed to overcome challenges and take advantage of existing opportunities. By developing a comprehensive curriculum that includes theory, practical skills, ethics and real-world applications, Indonesia can produce a workforce that is skilled and ready to compete in the era of artificial intelligence. The government, educational institutions and industry need to work together to accelerate the implementation of this curriculum to drive broader digitaltransformation across the country.